Towards a framework for understanding transitional green entrepreneurship. Issue 1 (2nd January 2016) - de Bruin, Anne
Abstract : The serious and complex environmental problems confronting today's society highlight the urgent need to effect a transition to a greener, ecologically sustainable future. This article presents a multilevel conceptual framework to advance understanding of this transition. Aligning with entrepreneurship as agency for social change, it captures the nature of transformative social change by employing different levels of social innovation (incremental, institutional and disruptive), and change (local, institutional and systemic change), associating each level with a type of social change agent, namely, green entrepreneurs or 'ecopreneurs'. The contemporary climate of social change overlays this integrative framework. Hence the temporal context links ecopreneurial activities to their political economy, socio-technological and cultural contexts, and the intensity of social action provides momentum for scaling their impact. New Zealand examples and insights drawn from the 2014 'Transitional green entrepreneurs: Re-thinking ecopreneurship for the 21st century, ' Symposium, in Sweden, illuminate the framework.